2013
DOI: 10.2174/1876326x01206010001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aging on Steroid Hormone Biosynthesis and Secretion

Abstract: Steroid hormones are lipophilic, low-molecular weight organic compounds all of which are derived from cholesterol. They are primarily synthesized by steroidogenic glands such as gonads (ovary and testis), the adrenal gland and, during pregnancy, by the placental trophoblasts. Limited steroid synthesis also takes place in the brain. Steroid hormones are crucial for the proper functioning of the body. They mediate a wide variety of vital physiological functions, ranging from maintaining normal reproductive funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 463 publications
2
12
0
2
Order By: Relevance
“…Extensive experimental evidence now indicates that aging in humans and animal models is associated with a general decline in steroid hormone production (Zaidi, et al 2012). Similarly, a number of in vitro studies have clearly shown that isolated adrenocortical cells and testicular Leydig cells (Zaidi et al 2012) of older rats of several different strains synthesize and secrete less steroid hormone in response to tropic hormone or its second messenger, cAMP, than do cells from young animals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive experimental evidence now indicates that aging in humans and animal models is associated with a general decline in steroid hormone production (Zaidi, et al 2012). Similarly, a number of in vitro studies have clearly shown that isolated adrenocortical cells and testicular Leydig cells (Zaidi et al 2012) of older rats of several different strains synthesize and secrete less steroid hormone in response to tropic hormone or its second messenger, cAMP, than do cells from young animals.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a number of in vitro studies have clearly shown that isolated adrenocortical cells and testicular Leydig cells (Zaidi et al 2012) of older rats of several different strains synthesize and secrete less steroid hormone in response to tropic hormone or its second messenger, cAMP, than do cells from young animals. These changes in steroid hormone production and secretion do not appear to be a function of reduced tropic hormone signaling or a defect in steroid hormone synthesizing enzymes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steroid hormones contain steroid nucleus and synthesized in the body from cholesterol , steroid hormones are a steroid that acts as hormones , it's endogenously derived from Cholesterol , the main classification of steroid hormones are corticosteroids ( typically made in the adrenal cortex , hence corticoids ) and sex steroids hormones which include androgens (male sex hormones) , oestrogens (female or follicular hormones) and gestogens (corpus luteum hormone ) [5]. Sex hormones belong to steroid hormones that are secreted by genital glands ( testes and ovaries ) and adrenal cortex and the placenta during pregnancy .…”
Section: Introductionmentioning
confidence: 99%
“…Помимо общеизвестной роли в регуляции половой функции, тестостерон обладает разносторонним стимулирующим действием на организм: активирует анаболические реакции, выражающиеся, в частности, в наращивании мышечной массы и уменьшении висцерального жира; поддерживает нормальное функционирование центральных нейронов; увеличивает экспрессию ряда регуляторных белков [6,7]. Показано его влияние на клеточный и гуморальный ответ иммунной системы [8].…”
Section: Introductionunclassified